KEBIASAAN BELAJAR SISWA BERPRESTASI DI SEKOLAH DASAR NEGERI 95 PEKANBARU - Dian Puspa Dewi; Zariul Antosa; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem that to be analyzed in the research were the habit of the student achievement at SD Negeri 95 Pekanbaru.this research as a descriptive research with qualitative and quantitative. The purpose of this research was to know student habits in learning the habit of the student achievement at SD Negeri 95 Pekanbaru. The research subject was 27 of student achievement in class IV, V and VI. The instrument of collecting data which were used questioner and observation sheet of indicator student habits are study preparation, following in learning, critically, stabilixed of material inlearning and the category of study habits in learning. The techniques of analyzing data in this research were scores tabulation questioner and observation sheet of student habit in learning and then the categorization of student academic result. The result witch find this research were student achievement in class IV, V and VI at SD Negeri 95 Pekanbaru had a good study habits. This is shown by questionnaire data and ibservation data as much 27 student there are 24 student had a good of study habits in learning with persentasge is 88,88% and 3 student had a enough of study habits with persentage is 11,11%. Based the result of this research was the student achievement at SD Negeri 95 Pekanbaru had a good of study habits in learning.Keywords : Study habits, Student Achievement